2023
DOI: 10.1177/07334648231191667
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization and Advance Care Planning among Older Adults Across Cognitive Levels

Abstract: This study examined the impact of advance care planning (ACP) on healthcare utilization among older adults with normal cognition and impaired cognition/dementia. Using datasets from the Health and Retirement Study, we conducted a cross-sectional study on 17,698 participants aged 51 years and older. Our analyses included survey descriptive and logistic regression procedures. ACP measures included a living will and durable power of attorney for healthcare. Healthcare utilization was measured using the days spent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Our results align with prior research, suggesting that disparities in healthcare persist, particularly concerning socioeconomic factors like age, race/ethnicity, and education (Brown et al, 2016;Mcmaughan et al, 2020;Rahemi, Malatyali, et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results align with prior research, suggesting that disparities in healthcare persist, particularly concerning socioeconomic factors like age, race/ethnicity, and education (Brown et al, 2016;Mcmaughan et al, 2020;Rahemi, Malatyali, et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…(BLINDED FOR REVIEW). Furthermore, those individuals with ACP were more likely to experience longer stays in hospitals, nursing homes, and home healthcare (Rahemi, Malatyali, et al, 2023).…”
Section: Social Determinants Of Health and Healthcare Utilization Dis...mentioning
confidence: 99%
“…Our findings were consistent with other researchers indicating that healthcare disparities persist in relation to variations in socioeconomic factors, particularly with respect to age, race/ethnicity, education, and rural location. 1,2325 Charron-Chenier and Mueller found that despite having greater clinical needs, households who were Black consistently demonstrated lower levels of healthcare use, even when controlling for socioeconomic, demographic, and healthcare insurance coverage differences between groups, 8 which underscores the existence of health disparities in both health outcomes and access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, this prevalence is elevated among individuals of Hispanic ethnicity, residing in rural areas, identifying as female, having lower levels of education, being of older age, and having co-morbidities. Overall, older adults from underrepresented and racial/ethnic minority groups have higher rates of chronic disease and cognitive impairment and lower rates of advance care planning (ACP) and comfort care at the end of life (EOL) [3, 6, 7]. It is imperative to explore the underlying causes of disparities in ACP and EOL care, aiming to eradicate inequities in healthcare based on factors such as race, ethnicity, and other personal identities.…”
Section: Introductionmentioning
confidence: 99%